Thermodynamic analysis of the direct converting of lead sulphide - M. Timucin (The Southern African Institute of Mining and Metallurgy, 1989)
High-temperature phase relations and thermodynamics of the condensed phase region of the Pb-S-O system at 1473 K were analysed by use of the available information. The sub-regular solution models on Pb-PbS and PbO-PbSO4 continuous melts were used in conjunction to generate a consistent set of thermodynamic and phase equilibrium conditions for the Pb-S-O system. The directions and distributions of conjugation lines between melts of this system were derived with relevant activity and composition data. The calculations permitted the thermodynamic analysis of direct lead smelting and the construction of isothermal reaction diagrams for the system in terms of oxygen and sulphur partial pressures at 1473 K.